Damage done by storm of September 14, 1900 to buildings and boats along the Snake River, Nome, Alaska, 1900 - Hester, Wilhelm, 1872-1947 (1900)
Caption on photo: Copyrighted by W. Hester, Seattle, 1900, 188, Showing destruction of property by recent storm along the Snake River, Nome. PH Coll 318.1044 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number